Insect pest complex and eco-friendly management of major insect pests of maize at medium altitude hills of Meghalaya - Lamare, Deebune Shilla; Thakur, N.S. Azad (Umiam : CPGS, CAU, 2012)
Insect pest complex of maize was studied by recording number of infested plants on ten plots during 2011. The observations on the seasonal incidence of different insect pest species were recorded by counting the number of infested plants per plot at weekly intervals from seed sowing till the harvest of the crop. The insect pests recorded were cut worm (Agrotis ipsilon Hufner), army worm (Spodoptera exempta Walker), shootfly (Atherigona soccata Rondani), stem borer (Chilo partellus Swinhoe), cob borer (Stenachroia elongella Walk.) and jassids (Zygnidia manaliensis Singh). Amongst the abiotic factors, evening relative humidity was found to favour the incidence of army worm and shootfly, whereas minimum temperature favoured the incidence of stem borer. Incidence of other pests was independent of the weather factors. In the present investigation, it was observed that early planting (1stweek April, 2011) of the crop results in less infestation of maize cob borer as compared to late sown crop (3rd week May,2011). However, stem borer infestation was minimum when the crop was sown late (3rd week May, 2011) in the season and maximum when sown early (1st week April, 2011). The management trials with different pesticides, botanicals and microbials revealed that amongst the synthetic insecticides, imidacloprid 17.8 SL (0.25 mill) was the most effective in reducing the infestation due to stem borer, followed by flubendiamide and endosulfan in their order of efficacy, whereas, amongst the botanicals, karanjin (2%) was found to be better than anonin (1%) followed by neem oil (0.3%). Amongst the microbials, spinosad 45 SC (1 mill) was found to be the most effective as compared to Bacillus thuringiensis and Beauveria bassiana. Among all the management techniques, imidacloprid 17.8 SL (0.25 mill) was found most effective in controlling the maize stem borer. Kernel yield was highest in plots treated with imidacloprid and is at par with plots treated with flubendiamide and endosulfan.
Keywords: Maize-Insect pests -- Meghalaya; Maize -- Eco-friendly management